Development of the PTEAM (Physics, Technology, Engineering, Art, Mathematics) Approach by applying the SOLO Taxonomy - Vivi Mardian; Didi Teguh Chandra (Proceeding International Conference on Religion, Science and Education, 2023)
Advances in science and technology cannot be separated from developments in physics. Physics discusses all natural phenomena both abstract and real. One of the right learning approaches to master literacy and numeracy skills is PTEAM. PTEAM stands for Physics, Technology, Engineering, Art and Mathematics. PTEAM can be implemented with the SOLO taxonomy. SOLO stands for Structure of the Observed Learning Outcome. There are five levels in the SOLO taxonomy namely SOLO 1 (pre-structural level), SOLO 2 (uni-structural level), SOLO 3 (multi-structural level), SOLO 4 (relational level), and SOLO 5 (extended abstract level). The PTEAM approach is a form of real implementation of the independent curriculum. PTEAM's main goal is to improve students' literacy and numeracy skills by applying engineering and technology themes to build the Unitary State of the Republic of Indonesia. PTEAM's learning innovations involve parents, teachers and the community.